Estudio técnico de una aplicación web para los servicios corporativos para la Institución “Centro Cristiano de Babahoyo” - Cedeño Hernandez, Anthony Leonardo (2021)
Currently, we live in the greatest boom in the technological age; With the different advances and computer developments that have emerged, it has caused humanity to choose to include new tools to help personal development in the community; As a great example, one of the best known is the use of smart phones worldwide, which went from being a personal luxury and became a priority tool for communication between human beings and society. From this perspective, this research was developed with the purpose of implementing computer technologies within the operational activities of the non-governmental institution Centro Cristiano de Babahoyo that provides services to society, in order to improve its benefits in favor of healthy living in the community. Babahoyense. Proposing in this case study the best business card for the institution by creating a web application, which increases its scope, prestige, quality and also allows users to increase their level of trust in the services it offers, through the internet, through different electronic devices such as cell phones, tablets and computers. In this study, the creation of a web application using php, html, perl and javascript technologies is proposed, which will be hosted on a web server, with total accessibility to it, from anywhere in the world, 27 hours a day; Putting into practice the knowledge acquired throughout the professional training, without involving unfathomable knowledge, in order to make the application more sensitive to future alterations in its functionality, but without leaving aside, the security controls in this system such as priority for safeguards the integrity of the information.